Contribuições para uma metodologia de avaliação da eficiência energética em iluminação de salas de aula - Fonseca, Suzana Damico (2009)
The several impacts from environmental degradations due to human activities and to the inadequate use of natural resources endanger our species. One of the factors contributing to this outcome is the growing worldwide demand for electric energy. In Brazil, according to the National Program of Conservation of Energy (Programa Nacional de Conservação de Energia Elétrica) - PROCEL, energy comsumption comprises, approximately, of 20% in artificial lighting, whose systems, in most cases, make use of obsolete and inefficient technologies. The Ministry of Mines and Energy (Ministério de Minas e Energia) estimates that the country has a huge potential for energy efficiency to be explored. In this paper, a methodology is presented to adjust the lighting system of a building aimed at public education to the requeriments of the Regulation of Voluntary Labeling of Higher Energy Efficiency for Commercial, Service and Public Buildings (Regulamentação de Etiquetagem Voluntária de Nível de Eficiência de Edifícios Comerciais, de Serviços e Públicos), according to the Law of Energy Efficiency (Lei de Eficiência Energética) Nº 10.295/01. For that purpose, classrooms of the Federal Technological University of Parana (Universidade Tecnológica Federal do Paraná), Curitiba Campus were analyzed. An assessment was done about the situation of the existing artificial lighting system and the potential use of daylighting in rooms was evaluated. The demand of electric energy for artificial lighting in each classroom was estimated according to the current situation and after improvement of the artificial lighting system to the requirements of regulations. As a result, a deficient artificial lighting system was found, a great potential for using daylighting and a promising economy in demand for energy were found, provided that lighting system was adapted to the current regulations. Considering the use of appropriate technologies for conservation and energy efficiency, suggestions for a simplified lighting design were proposed in order to - if implemented - reduce spending with the use of energy for lighting, provide comfort for the campus users and contribute, even in a modest way, for the preservation of natural resources and the environment.